The Orofacial Pain Clinic Questionnaire (EDOF-HC) in the evaluation and diagnosis of orofacial pain - SIQUEIRA, Silvia Regina Dowgan Tesseroli de; TEIXEIRA, Manoel Jacobsen; SIQUEIRA, José Tadeu Tesseroli de (Arquivos de Neuro-Psiquiatria, 2020)
Background: Diagnostic tools are necessary for the anamnesis and examination of orofacial pain, in order to fulfill diagnostic criteria and to screen potential causes of pain. Objective: To evaluate the Orofacial Pain Clinic Questionnaire (EDOF-HC) in the assessment and diagnosis of orofacial pain. Methods: Overall, 142 patients were evaluated and classified according to the criteria of the International Headache Society and International Association for the Study of Pain. All of them were evaluated with the EDOF-HC questionnaire, which consists of the orofacial and medical history, as well as the orofacial examination. Data were statistically analyzed with chi-square test and Bonferroni correction, one-way ANOVA with Tukey post hoc test, the two-step cluster and decision tree methods. Results: There were diferences in pain descriptors, pain in maximum mouth opening, number of trigger points, and history of previous surgery between the groups, which were classified into trigeminal neuralgia, burning mouth syndrome, temporomandibular disorders and trigeminal posttraumatic neuropathic pain with classification analysis. Conclusions: The EDOF-HC is a clinical supportive tool for the assessment of orofacial pain. The instrument may be used to support data collection from anamnesis and examination of patients according to the diagnostic criteria of most common orofacial conditions. It is also useful in the investigation of local and systemic abnormalities and contributes for the diagnosis of conditions that depend on exclusion criteria.
Keywords: Neuropathic pain; Orofacial Pain; Trigeminal Neuralgia; Temporomandibular Disorders; Diagnosis; Questionnaire